2011
DOI: 10.1111/j.2042-3306.2010.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two training protocols on Angiotensin I-converting enzyme (ACE) activity in horses

Abstract: Exercise training produced a gradual increase in enzymatic activity and might warrant the use of ACE as a tool for fitness monitoring. Angiotensin I-converting enzyme enzymatic activity in the plasma might be directly correlated to a change in genetic expression and that variability must be taken into account when evaluating results from horses undergoing a physical training programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…The reference values in humans are determined to vary between 13.3 and 63.9 U/L (Camos et al 2012). Studies in healthy horses which, as in our study, used FAPPG as substrate for analysis showed slightly higher values (Costa et al 2011, Afonso et al 2013, Munoz et al 2016 Our results agree with those of Costa et al (2016) (86 ± 18 U/L) and Afonso et al (2013) (59 ± 13.4 U/L). In contrast to that, Munoz et al (2016) showed slightly higher Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The reference values in humans are determined to vary between 13.3 and 63.9 U/L (Camos et al 2012). Studies in healthy horses which, as in our study, used FAPPG as substrate for analysis showed slightly higher values (Costa et al 2011, Afonso et al 2013, Munoz et al 2016 Our results agree with those of Costa et al (2016) (86 ± 18 U/L) and Afonso et al (2013) (59 ± 13.4 U/L). In contrast to that, Munoz et al (2016) showed slightly higher Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Effect of the ACE inhibitor enalapril on plasma ACE concentration in horses with left side heart valve insufficiency values (80 -120 U/L) (Costa et al 2011, Camos et al 2012, Munoz et al 2016).…”
Section: -mentioning
confidence: 99%
“…Alternatively, others have suggested using genetic screening or predictive modelling to identify those horses at greatest risk for catastrophic injuries, 4,[32][33][34] though the utility of these approaches have yet to be proven. While the detection of biomarkers for equine injuries has also been explored, [35][36][37][38][39] their use has not been widely adopted, despite some reported success. 40,41 Nevertheless, this overall shift from retrospective examination to a more proactive application of research signals a positive move towards catastrophic injury prevention, especially given recent headlines and negative attention regarding catastrophic injuries in North America.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have assessed ACE activity in response to ET are scarce. Costa et al 18 showed that 75 days of training in horses increased the circulating ACE activity. Our group also showed that rats subjected to high-volume ET increased plasma ACE activity 19 .…”
Section: Introdutionmentioning
confidence: 99%